HYPOKALEMIC PARALYSIS AS PRIMARY PRESENTATION OF SJÖGREN’S SYNDROME – A CLINICAL CASE REPORT - Sant Kumar; Aditya Prakash; Mahto, Binay Kumar; Rashmi Kumari (Student’s Journal of Health Research Africa, 2024)
Background Sjogren’s syndrome is an autoimmune rheumatic disease characterized by lymphocytic infiltration of exocrine glands resulting in multi-system presentations including xerostomia and dry eyes. Case Report A 47-year-old woman presented with generalized weakness, difficulty in walking, nausea, and pain abdomen. She had reduced muscle power (2/5) with reduced tone, and absent deep tendon reflexes in all four limbs. Further investigation revealed severe hypokalemia with metabolic acidosis. She was treated with intravenous potassium chloride and diagnosed with Sjogren’s syndrome based on her serology profile. After treatment, her condition improved. Conclusion Distal Renal Tubular Acidosis is a major cause of potassium loss in urine. Sjogren’s Syndrome is an important cause of Distal Renal Tubular Acidosis, which can present as severe hypokalemia. Although it commonly presents with symptoms like dry eyes and dry mouth, it can rarely present as Distal Renal Tubular Acidosis and hypokalemia as the primary presentation. Recommendation Sjogren’s syndrome should be suspected in patients with hypokalemia with features of Distal Renal Tubular Acidosis.